PENGARUH MEDIA SOSIAL FACEBOOK TERHADAP JATUHNYA REZIM PEMERINTAHAN HOSNI MUBARAK DI MESIR TAHUN 2011 - Ratih Maharani Eka Putri; Indra Pahlawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The objective of this research is to proof that social media nowadays not just as the source of information and communication but are use for a means of alternative to uproot a regime power. This research would describe one of the example of its issue in Egypt. Egyptian has a big problem of their thirty-year president, Hosni Mubarak. A lack of his leadership such as social inequality and corruption make Egyptian doing a big resistance started with social media as a alternative because Egyptian are constrained to do government critical directly.According to the facts, the perspective is pluralism approach is appropriate and could explain this reseacrh. Pluralists are assume that news on mass media is a reflection of the truth. Level analysis of this research is group. In some case, a specific group could involved of their government whether it is support or moving down. The main theory is from Dan Nimmo, Frustration or Scapegoat assume to create hatred cause of restrained rights then find another to be the scapegoat. Another technic is Bandwagon, to invite people to join and supporting a propaganda group because they have a good aim, some times the main person should get down to the field. Based on the research, Egypt Revolution was moved by a small group from facebook. In the begining this facebook group “We Are All Khaled Said” is just a sympathy from a man named Whael Ghonim to memoriam the victim of Egypt’s police violence, Khaled Said.The conclusion is from that small facebook group, many people join and speak up their opinion about a lack of president Hosni Mubarak. They can not tolerate any longer because his leadership is totally unfair. In the next more days member of facebook group account “We Are All Khaled Said” reached hundred-thousands people. Whael Ghonim and others pioneer of social media (facebook) take this chance as a opportunity to against back their government to uproot Hosni Mubarak.Keywords: assume, bandwagon, pluralism, propaganda, social media